The impact of oxygen consumption by the shrimp Litopenaeus vannamei according to body weight, temperature, salinity and stocking density on pond aeration: a simulation = Impacto do consumo de oxigênio do camarão Litopenaeus vannamei em relação ao peso corporal, temperatura, salinidade na aeração do viveiro: uma simulação - Luis Vinatea; Walter Muedas; Rafael Arantes (Acta Scientiarum: Biological Sciences, 2011)
A simulation was conducted to determinate the impact caused by thecombination of Litopenaeus vannamei respiratory rate (mg O2 shrimp-1 h-1), the behavior of SOTR (kg O2 h-1) of mechanical aerators as a function of salinity, as well as the oxygen consumption rate of the pond water and soil (mg O2 L-1 h-1) on the aeration of shrimp ponds (1, 10, 50 and 100 ha) stocked with different densities (10, 40 and 120 shrimp m-2), salinities (1, 13, 25 and 37 ppt), temperatures (20, 25 and 30°C), and shrimp wet weight (5, 10, 15 and 20 g). Results showed that under lower salinity, with larger shrimp, and higher stocking density, higher will be the quantity of required 2-HP aerators to keep dissolved oxygen over 50% saturation. In addition, under low salinity, with 5 and 10 g shrimp, independent of stocking density, more aerators per hectare are required and electricity cost is higher at 20°C and salinity 1 ppt. Less aerators and lower electricity cost was observed at 30°C, salinities of 25 and 37 ppt, and shrimp of 15 and 20 g. Baseado em estudos de respiração de Litopenaeus vannamei (mg O2 camarão-1 h-1), comportamento do Standard Oxygen Transfer Rate (SOTR, kg O2 h-1) de aeradores mecânicos em função da salinidade, assim como as taxas de respiração da água e do solo (mg O2 L-1 h-1), uma simulação foi realizada a fim de determinar o impacto que estas três variáveis juntas têm sobre a aeração de viveiros (1, 10, 50 e 100 ha), estocados com diferentes densidades (10, 40 e 120 camarões m-2) em salinidades de 1, 13, 25 e 37 ppm, temperaturas de 20, 25 e 30°C e peso úmido dos camarões de 5, 10, 15 e 20 g. Os resultados mostraram que em salinidades mais baixas, com animais maiores e maiores densidades de estocagem, maior será a quantidade de aeradores de 2 cvnecessários para manter o oxigênio dissolvido acima de 50% da saturação. Igualmente, em baixas salinidades e com camarões de 5 e 10 g, independente da densidade de estocagem, mais aeradores por hectare serão necessários, e o custo com eletricidade é máximo em temperatura e salinidade de 20°C e 1 ppm. A menor exigência de aeradores e de eletricidade é obtida a uma temperatura de 30°C, salinidades de 25 a 37 ppm e com camarões de 15 e 20 g.